ChemInform Abstract: Cu‐Catalyzed Consecutive Hydroxylation and Aerobic Oxidative Cycloetherification under Microwave Conditions: Entry to 2‐Arylbenzofuran‐3‐carboxylic Acids. Issue 36 (September 2015) - Xu, Tianlong; Zhang, Ensheng; Wang, Dejian; Wang, Yan; Zou, Yong
Abstract The characteristics of this tandem approach are the consecutive C—Br bond cleavage, C—H functionalization, and the C—O bond formation.